Evaluation of Osteoporosis in Sickle-Cell Patients by Using Dual- Energy X-ray Absorptiometry in Selective Hospital - ELsheekh, Mona Elhaj (International Journal of Innovative Research in Medical Science, 2023)
The study was attempted to evaluate osteoporosis in sickle-cell patients in the eastern province of Kingdom of Saudi Arabia by Using Dual-Energy X-ray Absorptiometry (DEXA). About 50 patients between 32 and 62 years old were taken as a sample size from Mouwasat Hospitals at Dammam and Qatif cities, who underwent for hip and spine DEXA scan. This research was a descriptive study which include 50 sickle cell patients who had gone under DEXA scan between January, 2016 and January, 2019. The study used simple sample randomization to obtained required data. The result of this study depending on mean BMD and T-score for both spine and hip region indicate osteoporosis. Osteoporosis was distributed as 86 % of female and 14% males of all participants. The incidence of osteoporosis at the spine was higher than hip which represented 56% of all osteoporosis cases. Additionally, the prevalence of osteoporosis among SCD patients increase with age; with the highest frequency recorded for participants aged between 52-62. Finally, only 16% of all participants reported a total hip joint replacement which was a poor result. The result of this study may not be validated in that it only included minimal portion of sickle cell patients in a short time. Further studies are recommended to develop this research and expand its findings.